The relationship of mean platelet volume with endogenous sex hormones and cardiovascular risk parameters in postmenopausal women - (:unkn) unknown (Yuzuncu Yil Universitesi Tip Fakultesi, 2014)
Evaluation of the relationship among mean platelet volume (MPV) and endogenous sex hormones and cardiovascular (CV) risk parameters. We designed a retrospective study in postmenopausal women. Patient charts were reviewed for the results of mean platelet volume, hormonal and biochemical parameters. MPV correlated only with white blood cell and platelet counts (r=-0.270, p=0.023 and r=-0.558, p=0.001 respectively). There was no statistically significant difference in MPV of patients with and without metabolic syndrome. We could not detect any relationship between MPV and endogenous sex hormones and parameters indicating higher CV risk.
Keywords: Cardiovascular disease; Endogenous sex hormones; Mean platelet volume; Postmenopausal women